Endophytic Bacteria Research in Indonesia: A Review - Hartanti, Dwi; Yunita, Risda (JURNAL PHARMASCIENCE, 2016)
In this review, a considerable amount of works that have been published on the endophytic bacteria isolated from host plants collected in Indonesia is reported. The objective of this review is to give an overview of the reported studies from the selection of host plants, the isolated bacteria, and the screened bioactivity of endophytic bacteria derived from Indonesian host plants.Keywords: bioactivity, endophytic bacteria, host plant, Indonesia.